Marx's theory of money : - Moseley, Fred (Palgrave Macmillan, 2005)
This book provides a contemporary assessment of Marx's theory of money. This theory is often praised as one of Marx's greatest achievements, especially when compared with either classical or neoclassical economics. On the other hand, Marx's theory of money has also been severely criticized, especially that is seems to require that money be a produced commodity. The contributors to the volume provide a wide-ranging and in-depth appraisal of the strengths and weaknesses of Marx's theory of money, compared to other theories of money.